The lady and the generals : Aung San Suu Kyi and Burma's struggle for freedom - Popham, Peter (London : Ebury Publishing, 2016)
Peter Popham's acclaimed biography of Aung San Suu Kyi, The Lady and the Peacock, concluded in November 2010, when she was finally released from seven and a half years of house arrest. But the greater drama was only just beginning: a wave of reforms that followed her meeting with the President, the release of most political prisoners, the partial lifting of censorship; then the re-registration of the National League for Democracy (NLD) as a political party, and Suu Kyi entering parliament for the first time. It was a rollercoaster ride during which Aung San Suu Kyi made several triumphant journeys round the world, and many young Burmese returned to the country to help with the ongoing creation of a civil society. However, progress slowed and the future seems not quite so bright. The racist expulsion of the Rohingyas was condemned round the globe and the military rulers are still very much in power. Though the NLD may continue to enjoy widespread support, Suu Kyi herself is unlikely to be allowed to stand as President in the Spring of 2016. Peppered with interviews and true stories which will bring this fascinating country, and its contemporary reality, vividly to life, Brave New Burma will be the only book you will need to read to follow this rapidly changing nation and the great woman who guides its future.
Includes bibliographical references (pages 405-412) and index.
Keywords: Aung San Suu Kyi; Burma -- Politics and government